2020
DOI: 10.1016/j.isci.2020.101751
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Subcapsular Sinus Microenvironment-On-A-Chip Modeling Shear Flow Relevant to Lymphatic Metastasis and Immune Cell Homing

Abstract: Summary A lymph node sinus-on-a-chip adhesion microfluidic platform that recapitulates the hydrodynamic microenvironment of the lymph node subcapsular sinus was engineered. This device was used to interrogate the effects of lymph node remodeling on cellular adhesion in fluid flow relevant to lymphatic metastasis. Wall shear stress levels analytically estimated and modeled after quiescent and diseased/inflamed lymph nodes were experimentally recapitulated using a flow-based microfluidic perfusion sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 103 publications
(165 reference statements)
4
40
0
1
Order By: Relevance
“…developed a LN subcapsular sinus-on-a-chip that recreated the LN hydrodynamic microenvironment and the effect of wall shear stress ( Fig. 4 A) [ 206 ]. They found that cell motility and adhesion are critical to immune cell recruitment and cancerous metastasis in the LN.…”
Section: Recent Progress On Lymph Node-mimicking Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…developed a LN subcapsular sinus-on-a-chip that recreated the LN hydrodynamic microenvironment and the effect of wall shear stress ( Fig. 4 A) [ 206 ]. They found that cell motility and adhesion are critical to immune cell recruitment and cancerous metastasis in the LN.…”
Section: Recent Progress On Lymph Node-mimicking Modelsmentioning
confidence: 99%
“…A) Schematic illustration of a subcapsular sinus microenvironment-mimicking, divergent parallel-plate microfluidic perfusion with an adhesion-molecule-functionalized, divergent portion. Reproduced with permission [ 206 ]. Copyright 2020, Elsevier.…”
Section: Recent Progress On Lymph Node-mimicking Modelsmentioning
confidence: 99%
“…The source of the cellular components is also an important point to consider. Some devices are validated using immortalized human cell lines as they are easy to obtain, manipulate and expand, are cost effective and allow experimental reproducibility (Moura Rosa et al, 2016;Birmingham et al, 2020;Shanti et al, 2020;Hallfors et al, 2021). Cell lines are well established models that can be easily modified to target and study molecules of interest.…”
Section: Technologies For Generating Lymph Nodes-on-chipmentioning
confidence: 99%
“…In a different attempt, Birmingham et al developed a novel microfluidic device to investigate the effect of subcapsular sinus remodeling (seen in inflammation) both biophysically (flow and structure) and biochemically (adhesion molecule expression) on human monocytic and metastatic cellular adhesion (Birmingham et al, 2020). The microfluidic device consists of a divergent adhesive microchannel cut from a 125 mm thick double sided adhesive tape and affixed to a PDMS block previously cured in a polystyrene tissue culture plate.…”
Section: Subcapsular Sinus Dynamicsmentioning
confidence: 99%
“…Conversely, other studies have revealed a pro-tumoral effect of these cells, mainly linked with their capacity to trigger and maintain the inflammatory response both in peripheral and lymphoid tissues 9,30,31 .…”
Section: Introductionmentioning
confidence: 96%